Atmospheric River Contributions to Ice Sheet Hydroclimate at the Last Glacial Maximum. Issue 1 (4th January 2023) - Skinner, Christopher B.; Lora, Juan M.; Tabor, Clay; Zhu, Jiang
Abstract: Atmospheric rivers (ARs) are an important driver of surface mass balance over today's Greenland and Antarctic ice sheets. Using paleoclimate simulations with the Community Earth System Model, we find ARs also had a key influence on the extensive ice sheets of the Last Glacial Maximum (LGM). ARs provide up to 53% of total precipitation along the margins of the eastern Laurentide ice sheet and up to 22%–27% of precipitation along the margins of the Patagonian, western Cordilleran, and western Fennoscandian ice sheets. Despite overall cold conditions at the LGM, surface temperatures during AR events are often above freezing, resulting in more rain than snow along ice sheet margins and conditions that promote surface melt. The results suggest ARs may have had an important role in ice sheet growth and melt during previous glacial periods and may have accelerated ice sheet retreat following the LGM. Plain Language Summary: During the Last Glacial Maximum (∼21, 000 years ago), ice sheets covered much of northern North America, Fennoscandia, and the Patagonian Andes. Using climate model simulations, we find that much of the precipitation that fell on the margins of these ice sheets came from transient, narrow corridors of atmospheric moisture known as atmospheric rivers. The atmospheric rivers were important in driving ice sheet accumulation during cold seasons, and ice sheet melt during warm seasons. The results suggest that atmospheric rivers may have had a role in driving the movement of ice sheets during Earth's past. Key Points: Atmospheric rivers were less frequent and supplied less precipitation globally during the Last Glacial Maximum (LGM) Over land, atmospheric river precipitation peaked along the margins of the extratropical ice sheets Atmospheric rivers were important contributors to the surface mass balance of LGM ice sheets